Caries risk factors based on cariogram among male smokers aged 15-24 years in Temanggung, Central Java, Indonesia - Agung Widyagdo; Bambang Priyono; Lisdrianto Hanindriyo (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Temanggung Regency in Central Java is an area with an extensive tobacco farming, allowing its residents to have ease of access to cigarettes. In addition, it has become a tradition for locals in this area to serve any visiting guest with cigarettes. Adolescents start smoking to cope with the psychosocial crisis during their development, particularly when they try to find their identity. Smoking is, in fact, a risk factor for dental caries, so the adolescents in Temanggung have a quite high prevalence of caries. Thus, this study aimed to determine the sequence of the risk factors affecting the caries risk based on cariogram among male smokers aged 15-24 years (adolescents). This was a quantitative observational study with a cross sectional design. There were 152 subjects (n= 152) selected using a proportionate clustered random sampling out of the total population (316 adolescents). The research was carried out with a clinical examination of the oral cavity, measuring salivary secretions, examining the amount of plaque, and examining DMF-T. Scoring was done using a caliogram application. The results of this study showed that 81.3% of the adolescents had a moderate caries risk, while 18.1% of them had a high caries risk. The sequence of the risk factors affecting the caries risk based on cariogram was bacteria (22.90%), susceptibility (19.39%), dietary habits (12.09%), and other influencing conditions (7.55%).